Análise da autocicatrização de diferentes tipos de concretos com vistas à durabilidade, por meio do ensaio de migração acelerada de íons cloreto - Paigel, Gabriel Agrisi (2025)
This study evaluates the phenomenon of self-healing in concrete with mineral additions and a crystalline admixture to understand its impact on durability, especially in aggressive conditions like those exposed to chloride ions. Mix designs with ground granulated blast-furnace slag, fly ash, a crystalline admixture, and a reference mix with high-early-strength Portland cement were analyzed in both uncracked and cracked samples, with crack widths less than 0.2 mm and between 0.3 and 0.4 mm. The methodology included chloride migration tests (NT BUILD 492), electrical resistivity measurements, stereoscopic microscopy, and, as a complement, X-ray diffraction (XRD) analyses to verify the ability of these materials to resist the penetration of deleterious agents and promote crack sealing. The results indicated that all materials showed some degree of visible self-healing. Concrete with blast-furnace slag stood out for its high resistance to chloride penetration, with a reduction of about 40% in penetration depth compared to the concrete with the crystalline admixture, in addition to showing higher electrical resistivity. In terms of self-healing, the concretes with fly ash and the crystalline admixture showed the best performance, while the slag demonstrated an intermediate behavior. The combined analysis of microscopy and XRD confirmed the formation of calcium carbonate (CaCO₃) as the main sealing product. The statistical analysis showed that the concrete's composition significantly influences its resistance to chloride penetration, while the crack width, within the studied ranges, did not have a relevant impact on the healing capacity. It is concluded that the use of mineral additions and specific admixtures is an effective strategy for producing more durable, resilient, and sustainable concrete.